Copper, zinc, and manganese niobates (CuNb2O6, ZnNb2O6, and MnNb2O6): structural characteristics, Li+ storage properties, and working mechanisms. Issue 17 (3rd August 2020) - Lee, Sung-Yun; Lim, An Seop; Kwon, Yong Min; Cho, Kuk Young; Yoon, Sukeun
Abstract : Niobium-based oxides are considered promising anode materials for Li-ion batteries due to their high capacities, good cyclability, and excellent safety. Abstract : Niobium-based oxides are considered promising anode materials for Li-ion batteries due to their high capacities, good cyclability, and excellent safety. Here, CuNb2 O6, ZnNb2 O6, and MnNb2 O6 niobate nanoparticles were prepared using a solvothermal method followed by heat treatment, and their electrochemical properties as anode materials for Li-ion batteries were explored. These CuNb2 O6, ZnNb2 O6, and MnNb2 O6 nanoparticles have BET surface areas of 3.17–11.53 m 2 g −1 . As anode materials, these nanoparticles display high reversible capacities of 256, 309, and 352 mA h g −1, respectively, at C/10; in particular, the excellent capacity retention rates of the CuNb2 O6 nanoparticle sample at 5C and 10C are 158 and 131 mA h g −1, respectively. After the first cycle, the Li-ion diffusion coefficients lie between ∼1.6 × 10 −7 and ∼2.1 × 10 −10 cm 2 s −1, which effectively promotes Li-ion uptake. Ex situ X-ray diffractometry provides insight into the insertion reaction by monitoring the changes in the crystal structures of the niobate samples during charge–discharge processes. We demonstrate that these niobate nanoparticle samples are possible alternative anode materials for use in rechargeable batteries.